Pengembangan Aplikasi RasulEdu Berbasis Android untuk Meningkatkan Literasi Digital pada Pembelajaran PAI Materi Sejarah Dakwah Rasulullah di SMP Negeri 1 Palangka Raya - Khalilurrahman, Muhammad; Jasiah, Jasiah; Azis, Abdul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to develop an Android-based learning application called RasulEdu to support Islamic Education (PAI) learning, particularly the topic of the Prophetic Mission History for seventh-grade students at SMP Negeri 1 Palangka Raya. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of needs analysis, design, development, implementation, and evaluation. The application’s visual elements were designed using Canva, while the development process utilized Smart App Creator. Product validation was conducted by experts in Islamic material, instructional media, and educational technology. Data analysis covered product feasibility assessment and measurement of digital literacy improvement through pretest–posttest. The validation results indicated a feasibility score of 91%, categorized as highly feasible. Field testing involving 30 students showed an increase in the average digital literacy score from 65.3 to 84.7. These findings demonstrate that RasulEdu is effective in enhancing students’ digital skills and understanding of the Prophetic mission material. Overall, the application serves as an interactive and relevant digital learning tool that supports PAI instruction in the modern educational setting.